Filtered cathodic arc deposition with ion-species-selective bias - Anders A. (2014)
A dual-cathode arc plasma source was combined with a computer-controlled bias amplifier to synchronize substrate bias with the pulsed production of plasma. In this way, bias can be applied in a material-selective way. The principle has been applied to the synthesis of metal-doped diamondlike carbon films, where the bias was applied and adjusted when the carbon plasma was condensing and the substrate was at ground when the metal was incorporated. In doing so, excessive sputtering by energetic metal ions can be avoided while the s p3 s p2 ratio can be adjusted. It is shown that the resistivity of the film can be tuned by this species-selective bias; Raman spectroscopy was used to confirm expected changes of the amorphous ta-C:Mo films. The species-selective bias principle could be extended to multiple material plasma sources and complex materials. © 2007 American Institute of Physics.